2004
DOI: 10.1002/bin.163
|View full text |Cite
|
Sign up to set email alerts
|

A further comparison of external control and problem‐solving interventions to teach social skills to adults with intellectual disabilities

Abstract: We compared the effectiveness of a problem-solving and an external control intervention to teach social skills to two adults with mild intellectual disabilities. Each participant received the problem-solving intervention with one social skill and the external control intervention with another social skill. The comparative effectiveness of the social skill training protocols was evaluated using individual participant alternating treatment designs. Overall, there seemed to be little difference between the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Perhaps the effect of appropriate social problem-solving strategies on behavior could be improved by including cognitive behavioral interventions adapted to the developmental level of these children. Indeed, cognitive behavioral intervention programs focused on social problem-solving skills have proven effective with children who have externalizing problems and average intelligence (e.g., Lochman & Wells, 2002;O'Reilly, Lancioni, Sigafoos, Green, et al, 2004;Zonnevylle-Bender, Matthys, Van de Wiel, & Lochman, 2007). However, training of the reflective response decision processes may only be effective when the generation of various response alternatives has been explicitly emphasized and trained and if evaluation and selection of response alternatives can be linked to response generation.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the effect of appropriate social problem-solving strategies on behavior could be improved by including cognitive behavioral interventions adapted to the developmental level of these children. Indeed, cognitive behavioral intervention programs focused on social problem-solving skills have proven effective with children who have externalizing problems and average intelligence (e.g., Lochman & Wells, 2002;O'Reilly, Lancioni, Sigafoos, Green, et al, 2004;Zonnevylle-Bender, Matthys, Van de Wiel, & Lochman, 2007). However, training of the reflective response decision processes may only be effective when the generation of various response alternatives has been explicitly emphasized and trained and if evaluation and selection of response alternatives can be linked to response generation.…”
Section: Discussionmentioning
confidence: 99%
“…One may wonder whether the part of these programmes concerning response decision is useful for children with MID. Research indicated that training in SIP improves social‐problem solving skills (O’Reilly et al. 2004a,b) and decreases aggressive behaviour in people with MID (Taylor et al.…”
Section: Discussionmentioning
confidence: 99%